Dermatophytosis: a 16-year retrospective study in a metropolitan area in southern Brazil - Heidrich, Daiane; Garcia, Marcelo Rocha; Stopiglia, Cheila Denise Ottonelli; Magagnin, Cibele Massotti; Daboit, Tatiane Caroline; Vetoratto, Gerson; Schwartz, Joel; Amaro, Taís Guarienti; Scroferneker, Maria Lúcia (The Journal of Infection in Developing Countries, 2015)
Introduction: Dermatophytoses are considered a public health problem. The objectives of this study were to determine the evolution of their prevalence in the metropolitan area of Porto Alegre, Brazil, and to analyze the dermatophyte species distribution according to body site and demographic characteristics of the patients. Methodology: This work was a retrospective analysis of data from patients attending a tertiary care hospital during 1996–2011. Results: There were 9,048 cases with cultures positive for dermatophytes. Trichophyton rubrum occurred in 59.6% of the cases, followed by Trichophyton interdigitale (34%), Microsporum canis (2.6%), Epidermophyton floccosum (1.5%), Microsporum gypseum (1.3%), and Trichophyton tonsurans (0.9%). The angular coefficients for T. interdigitale, E. floccosum, T. rubrum, and M. canis were +1.119, +0.211, -0.826 and -0.324% per year, respectively. Males presented higher prevalence of infection (79.3% versus 53.9%). Tinea unguium occurred in 48.5% of the cases, followed by tinea pedis (33.1%). T. rubrum was the predominant species in all regions of the body except the scalp, where M. canis was responsible for 75% of the cases. Conclusion: Monitoring of the evolution of dermatophytosis tracks changes in prevalence over the years and may assist practical measures for the public health control of this disease.